Relationships between binge eating disorder, anxiety and depression in medical students during military conflict - Yuryeva, Людмила; Ogorenko, Вікторія; Shornikov, Андрій; Kokashynskyi, Віктор (Psychosomatic Medicine and General Practice, 2022)
Binge eating disorder (BED) is an eating disorder characterized by loss of control over eating that is exacerbated during stressful events. Under the conditions of war, the population of Ukraine experiences significant distress, which affects the mental state and can lead to a loss of control over food. The aim of the work was to study the indicators of BED, anxiety and depression during the military conflict among medical students. A one-time cross-sectional epidemiological study of students of the Dnipro State Medical University was conducted. The questionnaire included questions on complaints, DSM-5 BED criteria, the BES, the Patient Health Questionnaire (PHQ-9), and the Generalized Anxiety Disorder (GAD-7) scale. 62 medical students were examined, with an average age of 21.6±1.5 years, most of them female (49/62). The prevalence of BED was 17.7% (11/62) using the DSM-5 BED criteria alone and 11.3% (7/62) using the BES. Severe BED was not found in any of the students, but severe depression was observed in 9.7% (6/62) and severe anxiety in 3.2% (2/62) of cases. The prevalence of anxiety with GAD-7 ≥ 5 is 58% (36/62), with GAD-7 ≥ 10 - 18.3% (12/62). The prevalence of depression in PHQ-9 ≥ 5 was 66.1% (41/62) and in PHQ-9 ≥ 10 it was 30.7% (19/62). There was a strong direct correlation between anxiety and depression scores rs=0.6878 at p<0.001 (95% CI for r 0.5151–0.7932) and a moderate relationship between severe depression (PHQ-9≥10) and BED and relatively strong relationship between measures of anxiety and depression. It was found that the level of depression higher than 10 points increases the chances of developing BED by 7.3214 times (95% CI 1.2742–42.0683). The obtained data demonstrate the prevalence and significance of BED among students during extreme stressful events such as a pandemic, war, etc., which is confirmed by comparison with other similar studies.